Evaluating E-Learning Systems Using COBIT 5 Framework on APO and DSS Domains (A Case Study: SMPN 2 Medang Deras) - Lumbantobing, Dedi Seventino; Sihotang, Jay Idoan (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
SMPN 2 MEDANG DERAS is a public junior high school located on Access Road Kuala Tanjung Street, Batubara District, North Sumatra - 123456. SMPN 2 MEDANG DERAS implements the national curriculum (K13) with 17 classes, 33 subjects, 28 teachers, and 7 staff. SMPN 2 MEDANG DERAS has consistently been accredited Grade A. This study utilizes the COBIT 5 framework as a measure of efficiency in the Evaluation of E-Learning Services at SMPN 2 MEDANG DERAS. COBIT 5 is the latest innovation in techniques for managing and optimizing E-Learning performance in schools. And use globally accepted principles, practices, analysis, and models to help increase the trust and value of the service itself. Researchers implemented COBIT 5 in techniques for managing and optimizing E-Learning performance. Collecting data by conducting a questionnaire technique using two domains of COBIT 5, such as APO (Align, Plan, Organise) and DSS (Deliver, Service, Support). The purpose of this research is to measure strategy management and problem management, which can help improve identify the value of the capabilities of the services used to achieve the school’s vision and mission. Keywords : E-learning, COBIT 5, Align, Plan, Organise, Deliver, Service, Support